STRATEGI KEBUDAYAAN DALAM NEGARA HUKUM UNTUK MENYONGSONG ADAPTASI KEBIASAAN BARU - Adi Purnomo Santoso; Herman Herman (Jurnal Ilmu dan Budaya, 2020)
Culture is a study that points to rejection in humans from an anthropological point of view. As a living being who develops his ability from reason, man has the ability to imagine himself and the events that may occur against him, so that man can make choices and selections against various alternatives in his behavior to achieve optimal effectiveness in maintaining life against the cruelty of the surrounding nature. However, the ability of humans as a group to adapt to changes that occur, including in the midst of the current Covid-19 pandemic, is not the same between one group and another human group. In fact, in the era of new habit adaptation, adaptability plays an important role in reducing the depth of impact of the Covid-19 pandemic that targets not only the health sector, but all aspects of life. This research has several objectives. First, examine the urgency of cultural strategy in the nature of Indonesia's development as a legal State. Second, examine the role of cultural strategy in the era of adaptation of new habits. Third, examine the strengthening of the character of the nation in order to meet the era of adaptation of new habits with a cultural strategy approach.